Pattern distribution of fingerprints in three ethnic groups in Nueva Vizcaya - Cabalonga, Mary Therese N. (Animo Repository, 1991)
This research determines the pattern distribution of fingerprints in three ethnic groups in Nueva Vizcaya: the Gaddangs, the Isinays and the Ikalahans.This study was done in various towns in Nueva Vizcaya where the Gaddangs, the Isinays, and the Ikalahans live. The fingerprints of the members of these groups were collected from October, 1990 to January, 1991. Chi-square test for independent samples was used to analyze the data. Study revealed that every finger has its own and distinct pattern. There is no general pattern distribution of fingerprints in terms of the ten digits in each of the ethnic groups between males and females in all three ethnic groups among the fingers in each hand or even between corresponding fingers of the right and left in each of the Gaddangs, the Isinays and the Ikalahans. It also found out the loops were the highest type of fingerprint pattern, while the arches the least in all three ethnic groups. For pattern distribution between sex groups who were most in number among the male Isinay group.